2007
DOI: 10.1103/physrevc.76.065207
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nuclear parton distribution functions and their uncertainties at next-to-leading order

Abstract: Nuclear parton distribution functions (NPDFs) are determined by global analyses of experimental data on structure-function ratios F A 2 /F A 2 and Drell-Yan cross-section ratios σ A DY /σ A DY . The analyses are done in the leading order (LO) and next-to-leading order (NLO) of running coupling constant α s . Uncertainties of the NPDFs are estimated in both LO and NLO for finding possible NLO improvement. Valence-quark distributions are well determined, and antiquark distributions are also determined at x < 0.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
438
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 335 publications
(455 citation statements)
references
References 102 publications
(117 reference statements)
12
438
5
Order By: Relevance
“…The issue of uncertainties in parton distributions is becoming increasingly important especially in relation to precision tests of QCD. Discussions on uncertainties in nuclear parton distributions can be found in [46,48].…”
Section: Parton Distributions In Nuclei and Photonsmentioning
confidence: 99%
See 3 more Smart Citations
“…The issue of uncertainties in parton distributions is becoming increasingly important especially in relation to precision tests of QCD. Discussions on uncertainties in nuclear parton distributions can be found in [46,48].…”
Section: Parton Distributions In Nuclei and Photonsmentioning
confidence: 99%
“…Two sets are by Eskola, Paukunnen, and Salgado, namely EPS08 and EPS09 [47,48]. The third is the Hirai-Kumano-Nagai (HKN07) distributions [46]. While EPS08 is only to leading order (LO), both EPS09 and HKN07 are available up to next-to-leading order (NLO).…”
Section: Parton Distributions In Nuclei and Photonsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [74], it was shown that a Langevin-based heavy quark transport model can qualitatively explain the large suppression (and azimuthal anisotropy) of electrons from heavy flavor decays in Au+Au collisions. The model places a heavy quark into a thermal medium, and assumes that the interaction of the heavy quark with the medium can be described by uncorrelated momentum kicks.…”
Section: Elliptic Flowmentioning
confidence: 99%